Effect of Bovatec® and Synovex-S® implants on finishing steer performance - Lyle W. Lomas (Kansas Agricultural Experiment Station Research Reports, 1982)
Cattle fed Bovatec consumed 18.3% less feed and were 19.4% more efficient in feed conversion than controls, with no effect on gain. Synovex-S implants improved gain by 8.2% with no effect on feed intake and feed efficiency. The effects of Bovatec and Synovex-S were additive.
Keywords: Cattlemen' s Day; 1982; Report of progress (Kansas State University. Agricultural Experiment Station); 413; Beef; Implants; Steer; Performance